Development of Short Story Writing Teaching Materials in the Website - Christ Mulia Solomasi Laoli; Mara Untung Ritonga; Adi Sutopo (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
The limitations in short story writing skills in Indonesian language learning include students' compositions being too short, their ideas or concepts not being well-developed, limited vocabulary to string together their ideas, difficulties in organizing sentences, and lack of direction in their writing forms. Therefore, guidelines are needed to gather ideas and arrange them into coherent and cohesive paragraphs, thus improving students' writing skills. By enhancing writing skills, students can think creatively, communicate with readers, and deepen their understanding. This study aims to determine the validity and practicality of short story writing teaching materials in the form of a website that has been developed. This research is developmental research using the ADDIE development model with the research subjects being fourth-grade students at UPT SDN 060866 Medan. The research instruments used are validation questionnaires and response questionnaires. The results of the validity test by material experts showed a percentage of 94.59% with the conclusion of being in the